Cell autonomous or systemic EGFR blockade alters the immune‐environment in squamous cell carcinomas. Issue 11 (29th August 2016) - Mascia, Francesca; Schloemann, Derek T.; Cataisson, Christophe; McKinnon, Katherine M.; Krymskaya, Ludmila; Wolcott, Karen M.; Yuspa, Stuart H.
Abstract : Targeting mutations and amplifications in the EGFR has been successful precision therapy for cancers of the lung, oral cavity and gastrointestinal track. However, a systemic immune reaction manifested by dose‐limiting inflammation in the skin and gut has been a consistent adverse effect. To address the possibility that intra‐tumoral immune changes contribute to the anti‐cancer activity of EGFR inhibition, squamous cancers were produced by syngeneic orthografts of either EGFR null or wildtype mouse primary keratinocytes transduced with an oncogenic H‐ras retrovirus. Flow cytometric, RNA and Bioplex immunoassay analyses of the tumor immune milieu were performed. Cancers forming from keratinocytes genetically depleted of EGFR were smaller than wildtype cancers and had fewer infiltrating FoxP3 Treg cells, lower Foxp3 RNA and a lower percentage of CD4 PD1 positive cells indicating a tumor cell autonomous regulation of its microenvironment. Hosts bearing wildtype cancers treated with gefitinib for 1 week showed a trend for smaller tumors. In this short term pharmacological model, there was also a trend to reduced FoxP3 cells and FoxP3 RNA in the tumors of treated mice as well as a substantial increase in the ratio of IL‐1A/IL‐1RA transcripts. These results suggest that relatively brief systemic inhibition of EGFR signaling alters the immune environment of the targeted cancer. Together these data imply that an EGFR dependent Treg function supports the growth of squamous cancers and is a target for the therapeutic activity of EGFR inhibition. Abstract : What's new? Precision therapy targeting the epidermal growth factor receptor (EGFR) is effective in lung, oral cavity, and gastrointestinal cancer. However, a systemic immune reaction resulting in dose‐limiting inflammation in the skin and gut has been a consistent adverse effect. To determine whether immune effectors could contribute to the anti‐cancer response, here the authors produced in mice squamous cancers that were either genetically deleted of EGFR or subjected to systemic treatment with gefitinib. Tumor cell autonomous (genetic) or systemic (pharmacologic) inhibition of EGFR signaling reduced tumor growth and Treg infiltration in the microenvironment, suggesting that EGFR‐targeted cancer therapy may indeed involve immunomodulation.